Current state of Tugai vegetation of Akhangaran river basin - Azimov Ibrohim; Khujanazarov Uktam; Toylibaev Sultanbek; Berdibayeva Gulshat (BIO Web of Conferences)
The paper involves phytocenotic and floristic diversity of the biota of the ecosystems of Akhangaran River basin. The current state, structure, areas of vegetation, especially in tugai communities of the basin in recent years have changed significantly under the influence of various types of anthropogenic factors. The entire territory of the basin, especially along the floodplain of the rivers is covered with a dense network of roads, numerous mines, quarries, rest homes, reservoirs and have significant demographic resources, i.e. the basin is the most dynamic area in the Western Tien Shan, where all types of desertification occur. In order to preserve the current phytocenotic diversity of all types of vegetation, in particular tugai communities, the task is to conduct a cartographic inventory based on space data. The results show that tugai vegetation in the basin is the most degraded and strongly changed in composition, structure and area, which is not only reduced in places gradually destroyed, i.e. replaced by cultivated lands.